Inter Correlation and Path Coefficient Studies for Grain Yield and its Components in Pearl millet (Pennisetum glaucum (L.) R.Br.) - Sumanth, M; Sumathi, P; Vinodhana, N Kumari; Sathya, M (Annals of Arid Zone, 2016)
. Â